PENGARUH FAKTOR â FAKTOR PERUSAHAAN TERHADAP PENGUNGKAPAN SUKARELA DALAM LAPORAN TAHUNAN PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Aswatul Khasanah, 07.05.52.0041; Maryono, Maryono (Students Journal of Accounting and Banking, 2012)
This research is to analyze the effect of liquidity, leverage, firm size, NPM, and the status of the company there are variables in the voluntary disclosure manufacturing companies listed on the Stock Exchange.The population in this study is a manufacturing company listed on the Stock Exchange in the year 2006-2009. The sampling technique used purposive sampling method to publish financial statements and notes to the financial statements in 2006-2009 respectively, have positive earnings.The results showed that: (a) Liquidity and insignificant negative effect on voluntary disclosure. (B) Leverage positive andÂ  ignificant impact on voluntary disclosure. (C) The Company size has positive and significant impact on voluntary disclosure. (D) NPM influence negative and significant impact on voluntary disclosure. (e) status company and a significant negative effect on voluntary disclosure. Liquidity, leverage, firm size, NPM, and the status of the company together (simultaneously) a significant effect on voluntary disclosure variable.Keywords: liquidity, leverage, firm size, firm NPM and status, voluntary disclosure